1996
DOI: 10.1111/j.1751-0813.1996.tb07567.x
|View full text |Cite
|
Sign up to set email alerts
|

Field trial of a staphylococcal mastitis vaccine in dairy herds: clinical, subclinical and microbiological assessments

Abstract: The trial showed that the vaccine was efficacious in reducing the incidence of clinical mastitis and prevalence of subclinical mastitis in a herd that had a serious staphylococcal mastitis problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 6 publications
3
28
0
3
Order By: Relevance
“…Most mammary quarters of vaccinated animals showed no clinical signs of mastitis; however, in the unvaccinated animals most quarters developed clinical o subclinical mastitis. These results are in agreement with other studies which have demonstrated that vaccination can reduce both the development of clinical symptoms and the development of new subclinical mastitis infections (Pankey et al 1985, Watson 1992, Watson et al 1996, Middleton et al 2006, but disagree with others which have shown that vaccination did not significantly affect the rate of clinical mastitis (Tenhagen et al 2001). According to Rainard and Poutrel (1991), reduced severity of symptoms is probably mediated via antibodies neutralizing the S. aureus toxins, and this effect is easiest to generate with vaccination.…”
Section: Discussionsupporting
confidence: 66%
“…Most mammary quarters of vaccinated animals showed no clinical signs of mastitis; however, in the unvaccinated animals most quarters developed clinical o subclinical mastitis. These results are in agreement with other studies which have demonstrated that vaccination can reduce both the development of clinical symptoms and the development of new subclinical mastitis infections (Pankey et al 1985, Watson 1992, Watson et al 1996, Middleton et al 2006, but disagree with others which have shown that vaccination did not significantly affect the rate of clinical mastitis (Tenhagen et al 2001). According to Rainard and Poutrel (1991), reduced severity of symptoms is probably mediated via antibodies neutralizing the S. aureus toxins, and this effect is easiest to generate with vaccination.…”
Section: Discussionsupporting
confidence: 66%
“…A combined CP5 and CP8 conjugate vaccine has been evaluated in a phase III clinical study (6,30), and antibodies specific for CPs have been shown to protect against S. aureus infections in murine models (7). A number of vaccines, some also including various polysaccharide surface antigens, have been designed and used against S. aureus mastitis of dairy cows (14,23,39). Both CP5 conjugate and wholecell vaccines stimulate antibody responses in cattle (8,38).…”
mentioning
confidence: 99%
“…One possible explanation for the limited success of previous field trials (8,35) may lie in the approach utilized to construction of these vaccines. In fact, in most cases empirical criteria for vaccine administration have prevailed over previous systematic acquisition of basic knowledge on the type of immune responses that would be required in the mammary gland to prevent S. aureus Ima infections.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made to prevent S. aureus mastitis through vaccination. The efficacy of current experimental S. aureus vaccines, however, has not yet been fully demonstrated in field trials (4,8,37), although certain protection was achieved in bovine herds with high prevalence of S. aureus mastitis (35). Indeed, whereas available vaccines can induce high levels of circulating specific anti-S. aureus antibodies (21), they failed to reduce the incidence of new Ima infection or eliminate chronic mastitis (20,32,37).…”
mentioning
confidence: 99%